2012
DOI: 10.1038/nphys2220
|View full text |Cite
|
Sign up to set email alerts
|

New chiral phases of superfluid 3He stabilized by anisotropic silica aerogel

Abstract: He, that anisotropic disorder, engineered from highly porous silica aerogel, stabilizes a chiral superfluid state that otherwise would not exist. Furthermore, we find that the chiral axis of this state can be uniquely oriented with the application of a magnetic field perpendicular to the aerogel anisotropy axis. At sufficiently low temperature we observe a sharp transition from a uniformly oriented chiral state to a disordered structure consistent with locally ordered domains, contrary to expectations for a su… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
102
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(119 citation statements)
references
References 27 publications
16
102
1
Order By: Relevance
“…Consistent with expectations based on other characterization methods 13 the RSA appears to be anisotropic and recent reports indicate that this type of anisotropy stabilizes an anisotropic superfluid state. 4,29 Additionally, a second anisotropic superfluid state emerges at even lower temperatures where the theory indicates that this is the manifestation of a biaxial state. 30 However, the requirements of this theory are for the elastic mean-free-path anisotropy for 3 He quasiparticle scattering in the aerogel to be λ || < λ ⊥ in contrast to our findings for the elastic mean-free-path anisotropy for scattering of methanol molecules.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with expectations based on other characterization methods 13 the RSA appears to be anisotropic and recent reports indicate that this type of anisotropy stabilizes an anisotropic superfluid state. 4,29 Additionally, a second anisotropic superfluid state emerges at even lower temperatures where the theory indicates that this is the manifestation of a biaxial state. 30 However, the requirements of this theory are for the elastic mean-free-path anisotropy for 3 He quasiparticle scattering in the aerogel to be λ || < λ ⊥ in contrast to our findings for the elastic mean-free-path anisotropy for scattering of methanol molecules.…”
Section: Discussionmentioning
confidence: 99%
“…Our application of the methanol diffusion experiment has significance for recent discoveries in superfluid 3 He in anisotropic aerogel where the anisotropy is responsible for stabilizing new quantum states. 4 …”
mentioning
confidence: 99%
“…The self-charge conjugation relation (51) for Majorana fermions is satisfied only when the antiunitary particle-hole (or charge conjugation) operator C is…”
Section: Majorana Fermion and Non-abelian Statisticsmentioning
confidence: 99%
“…[45][46][47][48][49] New phase diagrams have also been proposed for aerogels. 50,51) (iv) The surface density of states peculiar to gapless quasiparticle states has already been observed in specific heat measurements and high-precision spectroscopy based on transverse acoustics under well-controlled surface conditions. [52][53][54][55][56][57][58] Motivated by puzzling issues on the intrinsic angular momentum paradox, investigations on the nontrivial momentum space topology were first initiated in 3 He by Stone et al 59,60) and Volovik,61,62) independently.…”
Section: Introductionmentioning
confidence: 96%
“…They are just two of many p-wave states each distinguished by unique broken symmetries and these are the only stable states in pure 3 He in low magnetic field [1]. However, new phases in this manifold have been reported for superfluid confined within an anisotropic external framework; in one case chiral states within positively strained 98% porous, silica aerogel [2] and in another, equal spin pairing states within nematically oriented alumina hydrate aerogels [3]. Additionally, for a negatively strained aerogel, obtained by compression, we found that the relative thermodynamic stability between the A and B-phases can be reversed resulting in an unusual tricritical point between A, B, and normal phases with a critical magnetic field of H c ≈ 100 mT [4].…”
mentioning
confidence: 99%